Novel NR/EPDM blends - Brown P S; Tinker A J (Journal of Rubber Research, 1999)
Vulcanisation of the NR phase of a NR/EPDM blend during mixing is effected by using a very active accelerated-sulphur cure system. The crosslinking of the NR phase, albeit at a low level, results in a change in the blend rheology. A change in the blend morphology accompanies this process; the EPDM is a disperse phase within a NR matrix in the control blend but is present as part of a co-continuous blend morphology in the dynamically vulcanised blend. The size of the domains of both polymers is also reduced in the dynamically vulcanised blend. When properly compounded with clay and oil, the dynamically vulcanised blends are readily processed, scoring 13+ in extrusion through a Garvey die. The properties of vulcanisates derived from these blends are generally good.
Keywords: Accelerated-sulphur cure system; EPM blends; Natural rubber blends